Public perception of the revitalization of Indonesian WaqfÂ Institution - Hidayah, Nur; Mutiara, Tira; Hosen, Muhamad Nadratuzzaman; Larasati, Diah; Wahab, Abdul (EKONOMIKA SYARIAH : Journal of Economic Studies, 2023)
Indonesian Waqf Institution (BWI/Badan Wakaf Indonesia) was formed based on Law Number 41 of 2004 concerning Waqf. BWI has a firm legal standing within the national legal structure. However, several articles in the Waqf Law have an unfavorable impact on the performance of BWI. Waqf's potential and actualization gap is still significant amidst low public trust in Nazir's governance. BWI is also considered not optimal in developing the potential of Waqf in Indonesia. This study aimed to determine public perceptions regarding the proposed revitalization of BWI duties, functions, and authorities in the more ideal Waqf Management rules. The data collection method used was a questionnaire distributed to the public. The data were analyzed by descriptive statistics. The results showed that the community less agreed with expanding the role of BWI. It is possible due to the lack of public knowledge regarding issues related to the management and development of Waqf that are currently occurring. The community has not been able to adapt to changes, and it tends to be challenging to revitalize BWI's duties, functions, and authorities in waqf regulations.Badan Wakaf Indonesia (BWI) dibentuk berdasarkan Undang-Undang Nomor 41 tahun 2004 tentang Wakaf. BWI memiliki kedudukan hukum yang kuat dalam struktur hukum nasional. Namun, beberapa pasal yang tercantum dalam Undang-Undang Wakaf justru berdampak kurang baik terhadap kinerja BWI. Gap potensi dan aktulisasi Wakaf dinilai masih sangat besar, ditengah rendahnya kepercayaan publik pada tata kelola Nazir. BWI juga dinilai belum optimal dalam mengembangkan potensi wakaf di Indonesia. Penelitian ini bertujuan untuk mengetahui persepsi masyarakat terkait adanya revitalisasi tugas, fungsi dan wewenang BWI dalam aturan Pengelolaan Wakaf yang lebih ideal. Metode pengumpulan data yang digunakan adalah kuesioner yang disebar kepada masyarakat. Data yang diperoleh dianalisis secara statistik deskriptif. Hasil penelitian menunjukan bahwa masyarakat kurang setuju dengan perluasan peran BWI. Hal ini dimungkinkan karena kurangnya pengetahuan masyarakat terkait isu permasalahan terkait pengelolaan dan pengembangan wakaf yang saat ini terjadi. Masyarakat belum dapat beradaptasi dengan perubahan dan cenderung enggan terhadap upaya revitalisasi tugas, fungsi dan wewenang BWI dalam regulasi wakaf.